Dynamic Effects of Energy Transition and Financial Development on Carbon Productivity: Empirical Evidence from Indonesia - Wicaksono, Ditto Satrio; Budiasih, Budiasih (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This study offers a new perspective on carbon productivity in Indonesia, exploring how energy transition and financial development influence carbon productivity in the short and long term. It provides valuable insights into the mechanisms driving a low-carbon economy, a topic which the existing literature does not fully cover. Research Objectives: This study aims to determine the dynamic effects of energy transition and financial development on carbon productivity. Research Method: An error-correction mechanism (ECM) was employed, using Indonesian data from 1982 to 2024. The selection of ECM was predicated on its demonstrated aptitude to discern the temporal dynamics of variables, both in the immediate and extended periods. Empirical Results: The results show that energy efficiency and renewable energy use improve carbon productivity. Financial development also has a positive effect, although its magnitude is modest. Energy efficiency is the most influential variable. Additional variables show that natural resource rent has a positive effect, while globalization is statistically insignificant. The error-correction term is negative and significant, confirming convergence toward a long-run equilibrium. Implications: The government must strengthen energy-efficiency policy, accelerate renewable energy deployment, expand green-oriented finance, and allocate natural resource revenues towards sustainable infrastructure and low-carbon investment. These measures support Indonesia’s development and net-zero transition. JEL Classification: Q4, Q5, O13, O16, O44